Pengembangan Profesi Guru Melalui Pelatihan PTK untuk Mengimplementasikan Model PBL dan PJBL - Roslaini Roslaini; Septi Fitri Meilana (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2023)
Problem-based learning (PBL) and project-based learning (PjBL) are learning models set by the Ministry of Education and Culture to be implemented in schools. Therefore, teachers are expected to be able to apply both models to achieve learning objectives at school. At SMAN 3 Tambusai Utara, Rokan Hulu, Riau, teachers are mostly not familiar with the implementation of PBL and PjBL yet. For this reason, the Uhamka PkM team organized a training to equip the teachers with skills to implement PBL and PjBL based on TPACK. In the training process, the teachers are given theoretical knowledge of PBL and PjBL followed by writing action research proposals. The training model is conducted online with synchronous and asynchronous activities using Zoom Meeting and Email. The training results show that the teachers can develop action research proposals with PBL and PjBL models based on TPACK. In other words, teachers are able to design proposals and select attractive digital media to support students' enthusiasm for learning.